Analysis of Coverage of Tuberculosis Prevention Therapy (TPT): Literature Review - Rahmalina, Septia; Darmawan, Ede Surya (UI Scholars Hub, 2026)
Tuberculosis Preventive Therapy (TPT) is a crucial intervention for tuberculosis (TB) control, particularly among high-risk groups such as household contacts of TB patients and people living with Human Immunodeficiency Virus (HIV). Despite being recommended by the World Health Organization (WHO), TPT implementation still faces challenges at the primary care level. This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method to review 11 articles published between 2021 and 2025 that were relevant to TPT implementation in various high-TB burden countries, including Indonesia. The main barriers identified were input (logistics, training), process (tracing, education, monitoring), and output (low TPT initiation and completion coverage). A community-based approach, integrated policy support, and the use of short regimens have been shown to increase program success. These findings underscore the need to strengthen input systems, community education, and harmonize national and regional policies to support optimal TPT implementation in primary care.